Risk analysis and assessment of information resources - Казмірчук, Світлана Володимирівна (Ukrainian Information Security Research Journal, 2013)
The construction of information security management system (ISMS), complex system of information security and other security systems require carrying out the analysis and security risk assessment. The existing assessment tools in its majority are based on statistical approaches. In many countries, both at the enterprise level and at the State level such statistics is not conducted. This limits the ability of existing tools, such as the use of different input data types for assessment. A known tool gives no the administration opportunity for risks analysis and risk assessment of a wide range of initial parameters. On t he basis of the proposed risk analysis and assessment method, which based on the use of the integrated model representation of the risk parameters allow to conduct an assessment in the deterministic and fuzzy conditions using ten parameters, which can be represented as numeric and linguistic form, it was implemented the software system of risk analysis and assessment of information resources losses. To verify the developed software product there were designed various situations connected with the information security resources. The received results confirm the adequacy of software response on value changes of estimated component under different environment conditions, while the risk value does not change significantly when the basis of estimated components is changed.